2022
DOI: 10.1111/acfi.12920
|View full text |Cite
|
Sign up to set email alerts
|

CEO organizational identification and corporate innovation investment

Abstract: Identity theory in economics reveals that organisational identification motivates managers to take actions that are strongly aligned with firm interests. Nevertheless, organisational identification may also play a role in personal incentives. Leveraging the availability of CEO organisational identification data from the national internal control survey of listed firms in China, we document a positive impact of CEO organisational identification on corporate innovation. We also find that the positive impact is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…(1) CEO organizational identification (CEO_OI) is added as a control variable in the regression model. Previous studies have shown that CEO_OI may affect other executives' organizational identification [75] and corporate innovation [12]. Therefore, the relationship between CFO organizational identification and corporate innovation may be driven by CEO_OI.…”
Section: Robustness Testsmentioning
confidence: 95%
See 3 more Smart Citations
“…(1) CEO organizational identification (CEO_OI) is added as a control variable in the regression model. Previous studies have shown that CEO_OI may affect other executives' organizational identification [75] and corporate innovation [12]. Therefore, the relationship between CFO organizational identification and corporate innovation may be driven by CEO_OI.…”
Section: Robustness Testsmentioning
confidence: 95%
“…Finally, there have been no significant changes in China's corporate governance guidelines since 2014, especially in terms of executive responsibilities. Therefore, the data still reflect the current situation, and new research results are continuously published by scholars using this data [12,30,[74][75][76]. The company patent information and financial data are from the China Stock Market and Accounting Research (CSMAR) database.…”
Section: Data Sources and Sample Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…They tend to be a competitive and sustainable strategic orientation in decision-making, avoiding the psychology of abandoning innovation due to unwillingness to bear the consequences of risk. Previous scholars, including Flammer and Bansal (2017), Nguyen (2018), and D. Du et al (2022), also concluded that appropriate equity incentives could inhibit the tendency of executives to seek quick success and instant benefit.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%